2023
DOI: 10.1186/s13578-023-01134-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor E4F1 dictates spermatogonial stem cell fate decisions by regulating mitochondrial functions and cell cycle progression

Rong-Ge Yan,
Zhen He,
Fei-Chen Wang
et al.

Abstract: Background Spermatogonial stem cells (SSCs) provide a foundation for robust and continual spermatogenesis in mammals. SSCs self-renew to maintain a functional stem cell pool and differentiate to supply committed progenitors. Metabolism acts as a crucial determinant of stem cell fates; however, factors linking metabolic programs to SSC development and maintenance are poorly understood. Results We analyzed the chromatin accessibility of undifferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Lie et al ( 2022) [33] reported also that reduced COX6C expression led to impaired COX enzyme activity, affecting mitochondrial ATP production and thus sperm motility in buffalo. Moreover, oxidative phosphorylation was found to be enriched in all undifferentiated spermatogonia subtypes studied, with significant differences in the relative abundances of Ndufv1 and Cox6c transcripts between control and E4f1-depleted spermatogonia, the latter condition leading to a progressive loss of undifferentiated spermatogonial cells [34]. Other studies highlighted the differential expression of COX6C, NDUFA5, NDUFS7, and NDUFV2 between progenitor and differentiating spermatogonia, too [35].…”
Section: Discussionmentioning
confidence: 94%
“…Lie et al ( 2022) [33] reported also that reduced COX6C expression led to impaired COX enzyme activity, affecting mitochondrial ATP production and thus sperm motility in buffalo. Moreover, oxidative phosphorylation was found to be enriched in all undifferentiated spermatogonia subtypes studied, with significant differences in the relative abundances of Ndufv1 and Cox6c transcripts between control and E4f1-depleted spermatogonia, the latter condition leading to a progressive loss of undifferentiated spermatogonial cells [34]. Other studies highlighted the differential expression of COX6C, NDUFA5, NDUFS7, and NDUFV2 between progenitor and differentiating spermatogonia, too [35].…”
Section: Discussionmentioning
confidence: 94%
“…An Overview of Novel Transcription Factors Involved in Spermatogonial Stem Cells DOI: http://dx.doi.org/10.5772/intechopen.1004178 induced by loss of E4F1 activity. P53 deletion in E4F1-deficient germ cells did not correct the abnormalities in SSC maintenance; rather, it merely momentarily stopped spermatogonial loss [35].…”
Section: Bioinformatic Analysis Of Tcf3: (A) Protein-protein Interact...mentioning
confidence: 92%
“…Yan et al examined undifferentiated spermatogonia's chromatin accessibility at the single-cell level, and they discovered 37 positive TF regulators that could play a part in determining the fates of SSCs [35]. The whole undifferentiated spermatogonial pool gradually disappears when the transcription factor E4F1, which is expressed in spermatogonia, is conditionally deleted in mouse germ cells.…”
Section: E4f1mentioning
confidence: 99%
“…Mice were treated with EdU (RIBOBIO, China) at a dosage of 50 mg/kg body weight via intraperitoneal injections 43 . Two hours after EdU injections, testes were collected and fixed in 4% PFA.…”
Section: Methodsmentioning
confidence: 99%